Pengaruh Kemampuan Kerja dan Pengalaman Kerja Terhadap Pengembangan Karir Pegawai pada Kantor Camat Asakota Kota Bima - Abduh Rahim; Firmansyah Kusumayadi; Ita Purnama (Indo Publishing, 2026)
This study aims to examine the effect of work ability and work experience on the career development of employees at the Asakota District Office, Bima City. The research employed a quantitative approach with an associative research design. The population consisted of 40 employees, all of whom were selected as the research sample using a saturated sampling (census) technique. Data were collected through questionnaires and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination, as well as t-test and F-test. The results revealed that work ability has a positive and significant effect on employee career development. In contrast, work experience does not have a positive and significant effect on career development when tested partially. However, work ability and work experience simultaneously have a positive and significant effect on employee career development, with a coefficient of determination (R²) of 0.736, indicating that 73.6% of the variation in career development is explained by the two independent variables, while the remaining 26.4% is influenced by other factors not examined in this study. These findings indicate that improving employees' work ability should be prioritized to support career development at the Asakota District Office, Bima City.